Evaluasi Pembelajaran Sekolah Dasar Berbasis Pendidikan Karakter dan Multikultural di SDN Poris Pelawad 9 - Ina Magdalena; Widya Nur Aini; Dian Chaerani Utami; Rahmah Wati Anzani (RC-INSTITUT, 2021)
Learning evaluation is an overarching concept that both relies on measurement and assessment to make a combined judgment or decision. The character of education and evaluation of multicultural learning in elementary schools is adjusted to the level of thinking of children in elementary schools. Where there is still the beginning of the abstract stage. Character education is a system of inculcating character values ​​to school members, which includes knowledge, awareness or willingness, and actions to implement these values, both from God Almighty, ourselves, others, the environment, and the nation so that humans perfect to be human. In fact, multicultural education is an integral part of all levels of education. Therefore, the inculcation of multicultural values ​​is ideally applied in all subjects in formal education.